QURANIC EXEGESIS AS SOCIAL CRITICISM: The Case of Tafsîr al-Azhâr - Daud, Ilyas (ULUL ALBAB Jurnal Studi Islam, 2020)
This paper examines one of Nusantara commentary books entitled Tafsîr al-Azhâr that is written by Hamka. By analyzing the contents of the commentary and tracing the historical roots of the birth of the work, this study shows that Hamka contextualises his interpretation as a criticism against the Sukarno regime. Among the critiques that he poses in his commentary suggest that Sukarno aligns to Communism and the political policies of his administration resonate to the interest of Communist while at the same time are detrimental to that of Muslims. From the historical perspective, there was, in fact, a conflict between Hamka and Sukarno concerning the issue of Communism. In other words, there is a close relationship between Sukarno’s affinity to Communism and Muslim’s conflict with Communists in Indonesia. In the development of tafsîr studies so far, tracing the interpretation material in the context of social criticism is considerably understatement. This is the reason why this study takes this approach. This study suggests that tafsîr (Quranic exegesis) is not just a task of understanding the divine message, but can also be a social critic.